2021
DOI: 10.1021/acssuschemeng.0c06657
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst-Free Organic Transformations under Visible-Light

Abstract: Pollutants from industry and chemical laboratories have harmful effects on human health and the environment. Concerns about this problem have led to the development of more versatile and sustainable protocols based on the principles of green chemistry. One of these innovative approaches is to carry out the reactions under visible-light sources without photocatalysts. This benign, simple, and cost-effective method, inspired by nature, could be a suitable alternative to some classical methods, and change the har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 169 publications
2
33
0
Order By: Relevance
“…55 Following this pioneering study, C-H arylations have been reported using metal-free photocatalysts ranging from organic molecules, [56][57][58][59][60] polymers, 61 and semiconductors, namely BP, 8 g-CN/rGO, 28 biocatalyst 62 and etc. 63 Given the benefits of this new area in organic synthesis, photoredox catalysis for the direct C-H bond functionalization is now one of the best attractive options. The production of aryl radicals by single-electron transfer (SET) to a convenient substrate is the key step of photoredox C-H functionalization.…”
Section: Introductionmentioning
confidence: 99%
“…55 Following this pioneering study, C-H arylations have been reported using metal-free photocatalysts ranging from organic molecules, [56][57][58][59][60] polymers, 61 and semiconductors, namely BP, 8 g-CN/rGO, 28 biocatalyst 62 and etc. 63 Given the benefits of this new area in organic synthesis, photoredox catalysis for the direct C-H bond functionalization is now one of the best attractive options. The production of aryl radicals by single-electron transfer (SET) to a convenient substrate is the key step of photoredox C-H functionalization.…”
Section: Introductionmentioning
confidence: 99%
“…9 Some exciting results under catalyst-free visiblelight-promoted reaction conditions have been published since 2017. 10 In recent years, efforts have been made for the site-selective synthesis and modification of bioactive scaffolds in order to increase their structural diversity and utilization. 11 Pyrimidines, an integral part of DNA and RNA, show diverse pharmacological applications as effective bactericides, antivirals, insecticides, fungicides, and medicines.…”
Section: Introductionmentioning
confidence: 99%
“…9 Some exciting results under catalyst-free visible-light-promoted reaction conditions have been published since 2017. 10…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes, in case of electron donor-acceptor (EDA) complexes, an electron-transfer event can occur by absorbing visible light without need of any photocatalyst. [10] The heterocyclic scaffolds comprise one of the largest research areas in organic chemistry and have always been on the frontline of attention due to their abundant uses in pharmaceutical fields. [11,12] The importance of heterocyclic compounds for biomedical and material science applications has led to an increase in the development of novel methods for their preparation.…”
Section: Introductionmentioning
confidence: 99%